eCM 2012
DOI: 10.22203/ecm.v023a21
|View full text |Cite
|
Sign up to set email alerts
|

Bone apposition to a titanium-zirconium alloy implant, as compared to two other titanium-containing implants

Abstract: Implants made of commercially pure titanium (cpTi) are widely and successfully used in dentistry. For certain indications, diameter-reduced Ti alloy implants with improved mechanical strength are highly desirable. The aim was to compare the osseointegration of titanium-zirconium (TiZr) and cpTi implants with a modifi ed sandblasted and acid-etched (SLActive) surface and with a Ti6Al4V alloy that was sand-blasted and acid-washed. Cylindrical implants with two, 0.75 mm deep, circumferential grooves were placed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
104
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 39 publications
8
104
1
3
Order By: Relevance
“…42 In a recent report using titanium based implants, it has been shown that in addition to the electronegativity of the implant surface, several other factors can also influence the osteoinduction process in vivo. 43 The advantages and limitations of individual alloying metals have also been described in our previous report, 28 where we had shown that alloying processes improved the mechanical strength of implant materials and made their properties similar to those of bone tissue. Based upon these criteria, we can conclude from our results that Mg-5Zr-Ca implant, which showed high compressive strength, was not suitable for osteointegration, whereas Mg-2Zr-5Sr and Mg-Zr-2Sr implants, tend to resemble natural bone in their properties due to decreased compressive strength.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…42 In a recent report using titanium based implants, it has been shown that in addition to the electronegativity of the implant surface, several other factors can also influence the osteoinduction process in vivo. 43 The advantages and limitations of individual alloying metals have also been described in our previous report, 28 where we had shown that alloying processes improved the mechanical strength of implant materials and made their properties similar to those of bone tissue. Based upon these criteria, we can conclude from our results that Mg-5Zr-Ca implant, which showed high compressive strength, was not suitable for osteointegration, whereas Mg-2Zr-5Sr and Mg-Zr-2Sr implants, tend to resemble natural bone in their properties due to decreased compressive strength.…”
supporting
confidence: 59%
“…In vivo evaluation becomes necessary to understand how the implant will perform in a physiological environment. Various physicochemical factors can play equally important roles in new bone induction, 43 therefore, no single property should be considered as the only criterion for selecting an implant material for orthopedic application. Our study highlights the importance of including Sr and excluding Ca in optimal combinations of Mg-Zr alloys to obtain good osteogenic outcome in rabbit bones.…”
mentioning
confidence: 99%
“…Another study in miniature pigs also reported no differences for BIC values for TiZr implants with a modSLA surface after 1, 2, 4 and 8 weeks of unloaded healing compared to c.p. Ti implants with a mod-SLA surface, whereas the amount of bony ingrowth into the implants' groves was increased after 4 and 8 weeks for TiZr [ 109 ]. Slightly but not signifi cantly increased BIC values for TiZrmodSLA implants in comparison to c.p.…”
Section: Modsla: On Particular Tizr Alloy Implantsmentioning
confidence: 88%
“…9.3 ). When investigating surface roughness parameters by performing quantitative surface analysis using confocal white-light microscopy ( Table 9.3 , [ 109 ]) and blue light laser and interferometer [ 107 ], signifi cant differences have been observed for the number of samples measured. However, the c.p.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…The cytotoxicity of V is reduced by alloying Ti with V [13]. Osteoblast cell adhesion is improved by alloying Ti with Zr [14][15][16], which is a nontoxic and nonallergic metal.…”
Section: Introductionmentioning
confidence: 99%